2010
DOI: 10.1002/bdrb.20268
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effect of gestational exposure to nonylphenol on F1 male rats

Abstract: Gestational exposure to nonylphenol might induce neurotoxic and reproductive toxic effects on F1 male rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…For example, NP exposure doses changed from 50 mg/kg/day to 200 mg/kg/day in our toxicological studies 46,47 . Specifically, our previous study shown that the concentration of NP measured in Xiangjiang River in Zunyi of China ranges from 0.174 to 3.411 μg/L 48 .…”
Section: Discussionmentioning
confidence: 97%
“…For example, NP exposure doses changed from 50 mg/kg/day to 200 mg/kg/day in our toxicological studies 46,47 . Specifically, our previous study shown that the concentration of NP measured in Xiangjiang River in Zunyi of China ranges from 0.174 to 3.411 μg/L 48 .…”
Section: Discussionmentioning
confidence: 97%
“…The spatial memory and learning parameters were defined according to the following criteria [11]: 1) escape latency, or duration to find the platform; 2) number of failures to reach the goal, or the total number of times the mouse failed to find the platform within 60 sec in four trials per day; 3) staying time in the quadrant of the goal area, or the cumulative time spent in the quadrant including the goal in the probe test.…”
Section: Behavioral Analyses In the Water Maze Testmentioning
confidence: 99%
“…In the lamb, it was demonstrated to inhibit the secretion of FSH in the fetus with a concomitant decrease in testis size and Sertoli cell number at birth (Sweeney et al, 2000). In adult males exposed in utero or neonatally to alkylphenols abnormalities in reproductive organs histology, reduced weight of the testis, epididymis and prostate, reduced testosterone level as well as increased number of abnormal sperm and decreased sperm production were observed (Aydoğan & Barlas, 2006;Jie et al, 2010;Lee, 1998;Yoshida et al, 2001). These alterations may result from both modulation of the hypothalamus-pituitary axis and direct estrogenic action in reproductive tissues (Yoshida et al, 2001).…”
Section: Environmental Xenoestrogens 421 Industrial Xenoestrogens: mentioning
confidence: 99%